HUBUNGAN ANTARA MOTIVASI KERJA DAN PENGAWASAN KERJA DENGAN PRODUKTIVITAS KERJA DOSEN DAN KARYAWAN AKADEMI KEPERAWATAN DAN KEBIDANAN PAMENANG PARE - Cahyono, Aris Dwi (Jurnal AKP, 2010)
Work motivation is to push against a person the employee to work as possible in order to achieveorganizational goals. Productive supervisory one characteristic is to be encouraging or motivating membersto be autonomous and responsible, and achievement. Supervision so that productive to say, if thesurveillance itself was contained to the employee motivation to work with high performance. Thus it isunderstood that labor productivity can be achieved if the employees are able to work efficiently.The objective of this study was to prove: (1) the correlation between work motivation with workproductivity, (2) the correlation between the supervisory working with work productivity, (3) the correlationbetween work motivation and monitoring work together with work productivity in the Faculty and StaffCollege Nursing and Midwifery Pamenang Pare.The method used in this study is the analysis of multiple correlation. In the study population was alecturer and employees Academy of Nursing and Midwifery Pamenang Pare with 46 samples. Instrumentused to collect data was questionnaire. Testing the validity and reliability of research instruments used bythe Internal Consistency Cronbach Alpha method. Analysis of the data used is the product momentcorrelation (Pearson) and multiple linear regression with two predictors for p-value and the value of F.The results obtained are: (1) there is a correlation between motivation to work with labor productivity(p-value = 0.000 <0.05), (2) there is a correlation between the supervisory working with the productivity oflabor (p-value = 0.000 <0.05), and ( 3) there is a correlation between work motivation and monitoring worktogether with labor productivity in the p-value of 0.000 which is smaller than 0.05 or 88.403 F calculated forthe larger than F table 3.23.Conclusions of the research is proven there is a correlation between motivation to work with laborproductivity, labor supervision with work productivity, and motivation to work and control work togetherwith labor productivity and Staff Lecturer in the College of Nursing and Midwifery Pamenang Pare.